Abnormal symmetric chelipeds in an specimen of snapping shrimp Synalpheus fritzmuelleri Coutiere, 1909 - Moraes, Isabela Ribeiro Rocha [UNESP]; Zacari, Larissa [UNESP]; Santos, Rafael de Carvalho; Rodrigues, Gabriel Fellipe Barros [UNESP]; Castilho, Antonio Leão [UNESP] (Cambridge University Press (CUP), 2024)
Morphological symmetry abnormalities in cheliped appendages of alpheid shrimps are extremely rare and poorly recorded in the literature. A symmetric minor cheliped were, for example, observed in queen females belonging to Synalpheus eusocial species. Symmetric major chelipeds were now described in Synalpheus fritzmuelleri individuals living in shallow Brazilian waters. These individuals were found in symbiotic association with the bryozoan Schizoporella sp. (biogenic substrate) adhering to the pilings of Ubatuba Bay docks, São Paulo State. Only one of 20 sampled S. fritzmuelleri individuals presented anomalous symmetric chelipeds. Based on carapace length, size, and morphological features, the analyzed specimens seemed to be juvenile; thus, the hypothesis of anomalous condition can be directly linked to genetic inhibition of the mechanism accounting for major cheliped development in this ontogeny phase. Studies like the present one often provide remarkable information on animal morphology and can be used as reference in evolutionary assessments to be conducted in the future.
Keywords: Alpheidae; major cheliped; morphology; snapping claw; symmetry